ICT Anxiety among Higher Secondary School Teachers: A Survey (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This study explores ICT (Information and Communication Technology) anxiety among higher secondary school teachers through a comprehensive survey. As technology continues to transform educational practices, understanding the factors contributing to ICT anxiety is essential for facilitating effective technology integration. The researcher used a normative survey as their methodology for this analysis. In order to have a greater grasp of the here and now, it entails documenting, analyzing, and interpreting data. Five hundred and twenty-nine pupils from different schools in the Thanjavur region of Tamil Nadu make up the current study. We used a basic random sampling strategy to choose our samples. On the likert-type scale, respondents are asked to rate each statement from "strongly agree" to "strongly disagree" on a five-point scale. Standard notation for these points is SA for Strongly Agree, A for Agree, UD for Undecided, DA for Disagree, and SDA for Strongly Disagree. A variety of subjective weights are applied to the various places on the scale. Take the positive statements as an example: 5, 4, 3, 2, and 1 in the order of Strongly Agree to Strongly Disagree responses. In this case, the Strongly Agree answer is 5 points weighted. When a person's scores for each item are added together, their total scores are obtained. In terms of their concern around information and communication technology (ICT), male and female instructors at the secondary level in both urban and rural areas did not vary significantly.